The Happiness of Evil (Res Publica. Revista de Historia de las Ideas Políticas, 2016)
This article aims to lay emphasis on how Thucydides, when he describes the war of Corcyra and explores its moral consequences, focuses on the innermost regions of the human condition, that dimension of the psyche which remains hidden and denied in social peace and prosperity. The result is evil fully manifested, that is to say, not the kind of evil we do sometimes unwillingly, sometimes out of necessity, safety, fear, etc. In fact, that essentially human evil appears when the explainable and necessary conditions cease to exist—it is the unjustified evil, which isolates its performer from all context, subdues his will, and, in return, provides him with the ecstasy of happiness that only absolute evil can provide.